Participation and representation in governing multiple-use marine ecosystems. Issue 4 (2nd October 2018) - Fudge, Maree
ABSTRACT: Stakeholder participation has become central to marine governance, a trend that is consistent with resource governance more broadly. Imperatives for increasing participation in marine governance reflect complex sociological trends, including population-driven change in coastal areas, increasing marine industry; climate-mediated changes in productivity; and decreasing trust in governing institutions. Despite this, marine governance research points to a paradox – efforts to increase participatory governance are leading towards decreasing legitimacy and low levels of trust in the governance system. This paper examines stakeholder perceptions of representation in the context of efforts to achieve effective participatory governance of a multiple-use marine commons: the D'Entrecasteaux-Huon Channel region in Tasmania, Australia. Political representation was found to be an essential component of stakeholders' assessment of the legitimacy of the governance of multiple-use marine systems. At the same time, representation was found to be a contradictory component that could not necessarily be settled by ideal type institutional rules for participation in governance. This paper suggests that rethinking how representation can be managed institutionally within the network context is warranted. It contributes to marine governance research by directly facing the complexity of representation in participatory initiatives, and signals a potential avenue for examining the challenges of participatory governance of shared marine systems.